Graph Structures for Knowledge Representation and Reasoning Second Interntional Workshop, GKR 2011, Barcelona, Spain, July 16, 2011. Revised Selected Papers - Croitoru, Madalina; Rudolph, Sebastian; Wilson, Nic; Howse, John; Corby, Olivier (Lecture Notes in Artificial Intelligence, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Workshop on Graph Structures for Knowledge Representation and Reasoning, GKR 2011, held in Barcelona, Spain, in July 2011 as satellite event of IJCAI 2011, the 22nd International Joint Conference on Artificial Intelligence. The 7 revised full papers presented together with 1 invited paper were carefully reviewed and selected from 12 submissions. The papers feature current research involved in the development and application of graph-based knowledge representation formalisms and reasoning techniques and investigate further developments of knowledge representation and reasoning graph based techniques. Topics addressed are such as: bayesian networks, semantic networks, conceptual graphs, formal concept analysis, cp-nets, gai-nets, euler diagrams, existential graphs all of which have been successfully used in a number of applications (semantic Web, recommender systems, bioinformatics etc.).